Pengaruh Layanan Perpustakaan Terhadap Minat Kunjung Pemustaka di Perpustakaan STIKES Mega Rezky Makassar - Habir, Habir (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2016)
Academic library has provided a variety of services. Its services are maintained for the end-users. The best servies are considered to all academic libraries around the world. The current study is an associative research and using quantitave approach to measure. The location of the study is in STIKE Mega Rezk Makassar library. The number of population was 926 users with the sample of the respondents were 255. The respondents were gathered by using proportianete stratified random sampling technique. The data was analysed with IBM SPSS v19. The study found that the library services were in good category with score 78,73% while users’ interest was in high category with score 79,05%. It has indeed 0,648 relationship between the library services and the library visit interest.